Understanding the Drivers of Economic Growth: Grounding Endogenous Economic Growth Models in Resource-Advantage Theory - Shelby D. Hunt (Contemporary Economics)
Foss (2012) provides an informed and informative comment on my article “Trust, Personal Moral Codes, and the Resource-Advantage Theory of Competition: Explaining Productivity, Economic Growth, and Wealth Creation” (Hunt, 2012). In general, his comment is highly supportive of both the theory and the arguments developed in my article. He does, however, raise certain issues that need to be addressed. These issues relate to the concept of total factor productivity, the role of institutions in promoting economic growth, and the importance of understanding how transaction costs impact entrepreneurship and economic growth. This reply focuses on his discussion of growth economics and endogenous economic growth models.